Ankenbrandt Turns 30: The Illusory Simplicity of the Domestic Relations Exception - Drew Gehman (Washington University Journal of Law and Policy, 2023)
Among the tools in a litigant’s toolbox is the ability to invoke diversity jurisdiction of the federal courts with just two simple requirements: complete diversity of the parties and damages in excess of the requisite amount in controversy. However, a puzzling exception exists to this wellknown rule of civil procedure: the domestic relations exception. Three decades ago, the decision in Ankenbrandt v. Richards showcased the force of the domestic relations exception. Despite the fact that Carol Ankenbrandt satisfied the requirements to invoke diversity jurisdiction, the district court dismissed her action because federal courts refuse to hear cases involving domestic issues. Since Ankenbrandt, a circuit split has continued to highlight the decision’s murkier details. This Note focuses on the lasting impact of Ankenbrandt in the thirty years since it was decided and argues that its legacy is not one worth celebrating. The author provides a rich historical analysis of the development of the domestic relations exception and the policy considerations underlying the Ankenbrandt decision, as well as the practical outcomes of its holding. Ultimately, this Note argues that the domestic relations exception in its current iteration fails to adequately advance its supposed goal of restricting all domestic matters from federal courts and instead has resulted in patchwork access to federal courts amongst married and unmarried litigants. Finally, this Note suggests that the most principles way for federal courts to decline jurisdiction is through abstention, rather than the troublesome domestic relations exception.
Keywords: Diversity Jurisdiction; Ankenbrandt; Civil Procedure; Domestic Relations; Federal Courts